PELATIHAN PEMBUATAN MEDIA DENGAN MEMANFAATKAN MEDIA BEKAS DI PAUD AR RAHMAN - Putri Lidiana Permata Sari; Sri Rahmah Dewi Saragih; Rahma Yunita Ansi; Sri Rahayu (STMIK Royal, 2018)
Abstract: The using of media in learning is very important to increase the mutualism of education as making a secondhand media from carton that was conducted in PAUD Ar Rahman. The training was conducted to increase the teacher’s understanding and teacher’s skill in developing their professionalism especially in designing a learning media from a secondhand like carton. The first activity that was conducted is observation by using interview technique to the teachers. Then it was continued by training activity. This activity is like a workshop that was started from presentation about the theory of arrangement a learning media from a secondhand material, accompaniment to all teachers in designing and developing learning media from a secondhand material. At the end of this activity, there was 70% participant that able to develop a learning media from a secondhand material individually.Keywords: Media, Secondhand, Teacher of PAUDAbstrak: Penggunaan media pembelajaran sangat diperlukan dalam kaitannya dengan peningkatan mutu pendidikan seperti pembuatan media bekas yang dilakukan di PAUD Ar Rahman. Pelatihan ini dilakukan untuk meningkatkan pemahaman dan keterampilan para guru dalm mengembangkan profsionalisme khususnya dalam pendesainan/ pengembangan media pembelajaran dari barang bekas berupa karton. Kegiatan pertama yang dilakukan adalah observasi dengan menggunakan teknik wawancara terhadap para guru. Kemudian dilanjutkan dengan pelatihan. Kegiatan ini berbentuk workshop dimulai dari presentasi tentang teori penyusunan media pembelajaran dari barang bekas, pendampingan terhadap guru dalam perancangan dan pendampingan bagi guru dalam pengembangan media pembelajaran dari barang bekas. Pada akhir kegiatan sebanyak 70% peserta yang dapat mengembangkan media pembelajaran dari barang bekas secara mandiri.Kata kunci: Media, Barang, Bekas, Guru PAUD